Korean Wave in Mexico. Sociodigital Networks and Fangagement (2021)
This proposal is based on the assumption of conceiving the Korean Wave as a cultural industry capable of massively producing, commercializing, and communicating cultural manifestations by incorporating new technological and digital resources used to spread messages on a larger scale. This fact has allowed the presence of various Korean cultural products, derived from Hallyu, in different parts of the world, as would be the case in some Latin American countries, and especially in Mexico. The ideas presented here are the result of an extensive bibliographic review and are part of a postgraduate research project whose main objective is focused on analyzing consumer practices by Mexican people who consider themselves fans of this industry. As will be shown throughout this proposal, the organized fans have played an extremely important role in the expansion and consumption of the different cultural manifestations of Hallyu. Thus, a large part of the information that makes up this text derives from the state of the art examined for the construction of the aforementioned project. It is also extracted from a series of empirical examples that have taken place, above all, in the Mexican context, which allow observing the close interactions between Korean celebrities and their fans, thanks to the usage and meaning that has been attributed to socio-digital networks today.